A Study to Assess the Effectiveness of Structured Teaching Program on Knowledge and Practice Regarding Nebulization in Children (0–5 year) among Student Nurses - Mangaiyarkarasi, Mrs.; Pandey, Eshpa; Keretta, Urmila (International Journal of Nursing Research, 2023)
Aims: The aim of the study was to access the knowledge and practice of student nurses toward nebulization therapy. Introduction: Nebulization is an important tool in the treatment of respiratory conditions. Nurses are primary health-care providers for using the nebulizers in a hospital setting. The examination of nurse’s knowledge and performance regarding the nebulizer therapy is of almost importance for proper nebulization. Methodology: The pre-experimental research design was conducted in this study. The total sample was 60 in this study. Purposive sample technique was used. The target population is student nurses. The area of setting is Government Medical College Hospital of Ambikapur (c.g.). Result: The data show that analysis of the knowledge score pre-test mean score was 9.75, mean percentage score was 1.66% and SD was 2.71, analysis of post-test knowledge mean score was 14.51, mean percentage 2% and SD was 1.76, and standard error was 0.412, paired “t” value was 6.85 that was found to significant at 0.05 level. Practice score and pre-test mean score was 13.08, mean percentage score was 54.5%, and SD was 2.37, analysis of post-test knowledge mean score was 17.08, mean percentage 71.16 and SD was1.42, and standard error was 0.35, paired “t” value was 11.42 that was found to significant at 0.05 level. Conclusion: After the detailed analysis, this study leads to following conclusion that is more effective in improving knowledge and practice on regarding nebulization therapy.